2015
DOI: 10.1007/s11356-015-5276-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting biofilm thickness and biofilm viability based on the concentration of carbon-nitrogen-phosphorus by support vector regression

Abstract: Current tools to predict biofilm thickness and viability in spatial distribution are poor, especially those based on chemical oxygen demand (COD), total nitrogen (TN), and total phosphate (TP) due to their limited data and complex calculations. Here, support vector regression (SVR) was used to predict biofilm thickness and viability in a reactor filled with carriers of crushed stone globular aggregates. Analyses combined confocal laser scanning microscopy and flow cytometry with Kriging interpolation revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For example, heterogeneity was ascribed to differences in treatment processes, e.g., treatment units (Ma et al, 2017; Bruno et al, 2018), filtration type (Pinto et al, 2012; Lautenschlager et al, 2014), or filtration media (Vignola et al, 2018). Also, changes in the exposure to disinfection and disinfectant residuals (Servais et al, 2004; Potgieter et al, 2018), as well as differences in the composition and quantity of nutrients (Niquette et al, 2001; Bester et al, 2010), radial-spatial orientation (Lin et al, 2016; Liu et al, 2017), and temperature (Liu et al, 2013) were shown to cause biogeographical heterogeneity. The most dramatic variations in drinking water systems occur in the built environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, heterogeneity was ascribed to differences in treatment processes, e.g., treatment units (Ma et al, 2017; Bruno et al, 2018), filtration type (Pinto et al, 2012; Lautenschlager et al, 2014), or filtration media (Vignola et al, 2018). Also, changes in the exposure to disinfection and disinfectant residuals (Servais et al, 2004; Potgieter et al, 2018), as well as differences in the composition and quantity of nutrients (Niquette et al, 2001; Bester et al, 2010), radial-spatial orientation (Lin et al, 2016; Liu et al, 2017), and temperature (Liu et al, 2013) were shown to cause biogeographical heterogeneity. The most dramatic variations in drinking water systems occur in the built environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, each system typically has warm and cold water outlets ( Figure 2), with hoses, taps, and various connected home appliances (e.g., a washing machine), all of which will potentially create unique and very different environments. From a microbiological point of view, bacteria that enter a building plumbing system from the DWDS experience an immediate and considerable change in environmental conditions, and it is common knowledge that a change in environmental conditions will often result in a change in bacterial numbers [40], viability [41], activity [42], and composition [43].…”
Section: The Microbiological Black Box Between the Water Meter And Thmentioning
confidence: 99%